The Global Snake Bite Initiative: an antidote for snake bite - Williams, David J. (2010)
Clinicians have for a long time witnessed the tragedy of injury, disability, and death from snake bite that is a daily occurrence in many parts of Africa, Asia, and Latin America. To many people living in these regions, including some of the world’s poorest communities, snake bite is an ever present occupational risk and environmental hazard, an additional penalty of poverty. Like malaria, dengue, tuberculosis, and parasitic diseases, the risk of snake bite is always present. Unlike many of these other public health risks, however, the burden of human suff ering caused by snake bite remains unrecognised, invisible, and unheard by the global public health community, forgotten by development agencies and governments alike. The problem is so underrated that it was only added to WHO’s list of neglected tropical diseases in April, 2009.